The Authors Reply - Hauskeller, Michael (The Hastings Center report, 2013)
A reply by the author of “Reflections from a Troubled Stream: Giubilini and Minerva on ‘After-Birth Abortion’” to “The Arguments Matter,” by Don Marquis, “The Importance of Rationality,” by G. Owen Schaeffer, and “Reasons and Freedom,” by Alberto Giubilini and Francesca Minerva.